THU0472 FAST3 (fibromyalgia assessment screening test): a composite index based on mdhaq provides clues to the presence of secondary fibromyalgia in patients with a primary diagnosis of rheumatoid arthritis at higher levels than identified in the medical record: a cross sectional study from routine care. (15th June 2017) - Castrejon, I; Gibson, K; Block, JA; Pincus, T
Abstract : Background: Secondary fibromyalgia (FM) is reported in 17% of RA patients 1, but may be under-recognized in patients with classical RA findings. A FAST3 (fibromyalgia assessment screening test) index based on 3 MDHAQ (Multidimensional Health Assessment Questionnaire) scores gives similar results to ACR fibromyalgia criteria based on a widespread pain questionnaire, 2 to assist in recognizing patients with secondary FM 3 . Objectives: To study patients with a primary diagnosis of RA seen in routine care for the proportion identified as having secondary FM according to a physician diagnosis in the medical record versus a FAST3 Index of MDHAQ scores. Methods: All patients complete an MDHAQ/RAPID3 at all visits in the waiting area in routine care. The MDHAQ includes 0–10 scores for physical function, pain, and patient global estimate, compiled into RAPID3, as well as a 0–48 RADAI self-report score of painful joints, and 0–60 symptom checklist. FAST3 has been developed previously as the 0–3 sum of 1 point each for 3 MDHAQ scores: pain VAS ≥6, RADAI ≥16, and symptom checklist ≥16. 3 FAST scores of ≥2/3 had >80% agreement with ACR FM criteria based on a widespread pain questionnaire 2 to identify secondary FM. 3 A random visit for each patient with a primary diagnosis of RA with complete data was studied. The number with a diagnosis of secondary FM in the medical record was compared to the number with FAST3 scores of 0, 1, 2, 3, and with each of the 3 FAST3 components. Receiver-operating characteristic (ROC) curves were generated to estimate sensitivity and specificity for each cut-point of the FAST3 score, using a diagnosis of secondary FM by the physician as the external criterion. Results: 287 patients with RA were studied, of whom 10 (3.3%) had a diagnosis of secondary FM by the physician in the medical record and 61 (22%) had FAST3 scores of 2 or 3 (Table), including 6 of 10 identified as having FM in the medical record. Overall, FAST3 was 0 in 161 RA patients (56%), 1 in 59 (20.6%), 2 in 46 (16%), and 3 in 21 (7.3%) (Table). Overall, 55 additional RA patients were identified by FAST3 versus the medical record as having possible secondary FM. The ROC area was 0.73 (95% CI, 0.57–0.89) (data not shown). Conclusions: The same MDHAQ used to score RAPID3 may also provide a FAST3 score as a screening tool for secondary FM in RA (and other) patients (including primary FM). Secondary FM may be under-diagnosed by clinicians in routine care. Further validation of FAST3 in other settings is needed. References: Wolfe F, et al. J Rheum 2011;31:695–700. Wolfe et al, J Rheumatol 2011;38:1113–22. Gibson K, et al. Arthritis Rheumatol. 2016; 68 (suppl. 10). Disclosure of Interest: I. Castrejon: None declared, K. Gibson: None declared, J. Block: None declared, T. Pincus Shareholder of: Health Report Services, Inc